Genomic Insight Into Lacticaseibacillus paracasei SP5, Reveals Genes and Gene Clusters of Probiotic Interest and Biotechnological Potential - Kiousi, Despoina Eugenia; Efstathiou, Christos; Tegopoulos, Konstantinos; Mantzourani, Ioanna; Alexopoulos, Athanasios; Plessas, Stavros; Kolovos, Petros; Koffa, Maria; Galanis, Alex (Frontiers in Microbiology, 2022)
The Lacticaseibacillus paracasei species is comprised by nomadic bacteria inhabiting a wide variety of ecological niches, from fermented foodstuffs to host-associated microenvironments. Lc. paracasei SP5 is a novel strain, originally isolated from kefir grains that presents desirable probiotic and biotechnological attributes. In this study, we applied genomic tools to further characterize the probiotic and biotechnological potential of the strain. Firstly, whole genome sequencing and assembly, were performed to construct the chromosome map of the strain and determine its genomic stability. Lc. paracasei SP5 carriers several insertion sequences, however no plasmids or mobile elements were detected. Furthermore, phylogenomic and comparative genomic analyses were utilized to study the nomadic attributes of the strain, and more specifically, its metabolic capacity and ability to withstand environmental stresses imposed during food processing and passage through the gastrointestinal (GI) tract. More specifically, Kyoto Encyclopedia of Genes and Genomes (KEGG) and Carbohydrate-active enzyme (CAZymes) analyses provided evidence for the ability of the stain to utilize an array of carbohydrates as growth substrates. Consequently, genes for heat, cold, osmotic shock, acidic pH, and bile salt tolerance were annotated. Importantly bioinformatic analysis showed that the novel strain does not harbor acquired antimicrobial resistance genes nor virulence factors, in agreement with previous experimental data. Putative bacteriocin biosynthesis clusters were identified using BAGEL4, suggesting its potential antimicrobial activity. Concerning microbe-host interactions, adhesins, moonlighting proteins, exopolysaccharide (EPS) biosynthesis genes and pilins mediating the adhesive phenotype were, also, pinpointed in the genome of Lc. paracasei SP5. Validation of this phenotype was performed by employing a microbiological method and confocal microscopy. Conclusively, Lc. paracasei SP5 harbors genes necessary for the manifestation of the probiotic character and application in the food industry. Upcoming studies will focus on the mechanisms of action of the novel strain at multiple levels.